PERAN LEMBAGA PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DALAM PENINGKATAN KAPASITAS PEREMPUAN DESA SEA KECAMATAN PINELENG KABUPATEN MINHASA - Morton ., Pakudek; Welson Marthen Wangke; Benu Olfie Liesje Susana (Sam Ratulangi University, 2018)
This study aims to find out how the role of the Family Welfare Empowerment Institution (PKK or FWE) in enhancing women's capacity through the 10 main programs of PKK and to find out how to increasewomen's capacity through the application of 10 main PKK programs. The location of this study was in the Sea from June to August 2018. Data collection was carried out by interview technique directly to 30 respondents based on the questionnaire prepared in advance. The results obtained from this study using the Likert scale analysis showed that the FWE (PKK) Institution of the Sea Village, Pineleng Sub-district, Minahasa District in increasing women's capacity based on the 10 main programs of Family Welfare Empowerment (PKK) was in a total score of 880 with an interpretation of 88.88 % or categorized as a play role, and the capacity of women in the Sea Village of Pinelang District, Minahasa District through the application of the 10 main programs of Family Welfare Empowerment in a total score of 1,021 with an interpretation of 87.26% or categorized as increasing.*eprm*.